2016
DOI: 10.1371/journal.pone.0150581
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rocking Movements on Respiration

Abstract: For centuries, rocking has been used to promote sleep in babies or toddlers. Recent research suggested that relaxation could play a role in facilitating the transition from waking to sleep during rocking. Breathing techniques are often used to promote relaxation. However, studies investigating head motions and body rotations showed that vestibular stimulation might elicit a vestibulo-respiratory response, leading to an increase in respiration frequency. An increase in respiration frequency would not be conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Consistent with previous observations in this study, overall sleep quality was significantly improved and day time sleepiness was significantly decreased following vestibular stimulation in male and female intervention groups. Although linear swinging and rocking chairs are well known to induce sleep, the pathways involved are not clearly known [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with previous observations in this study, overall sleep quality was significantly improved and day time sleepiness was significantly decreased following vestibular stimulation in male and female intervention groups. Although linear swinging and rocking chairs are well known to induce sleep, the pathways involved are not clearly known [9].…”
Section: Discussionmentioning
confidence: 99%
“…Emotional eating, uncontrolled eating and increased tendency to eat nonnutritious food were observed in young adults with high stress [8]. Vestibular stimulation promotes sleep through relaxation effect, through direct and indirect connections with amygdala, sensory systems, thalamus, hypothalamus and brain stem areas [9]. Swinging has been reported to alter physiological parameters of sleep.…”
Section: Introductionmentioning
confidence: 99%
“…First, in work, Vaessen and colleagues [55] search for distinct brain responses in fMRI data to the visual stimuli of full body movements, which differ in terms of motor planning. Second, several researchers observed spontaneous synchronization between the full-body movements and respiratory rhythms [4,14,35]. This phenomena is often explained with the concept of entrainment, i.e., by a temporal locking process in which one system's motion or signal frequency entrains the frequency of another system [53].…”
Section: Movement Testbedmentioning
confidence: 99%
“…A study by Omlin et al. () showed that otolith stimulation by rocking movements along the longitudinal axis of the body affected human respiratory frequency. Monahan, Sharpe, Drury, Ertl, & Ray () found that stimulation of the semicircular canals, but not the otolith organs, increased ventilation in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Although natural and caloric stimulations of the semicircular canals have been proved to induce alterations in respiration (Jauregui-Renaud, Gresty, Reynolds, & Bronstein, 2001;Jauregui-Renaud, Yarrow, Oliver, Gresty, & Bronstein, 2000), very little is known about the physiological importance and functional characteristics of the relationship between the otolithic and respiratory systems. A study by Omlin et al (2016) showed that otolith stimulation by rocking movements along the longitudinal axis of the body affected human New Findings…”
Section: Introductionmentioning
confidence: 99%